Strategi Manajemen Talenta dalam Mempertahankan Generasi Milenial di SMK Negeri 10 Luwu - Header Header; Ariska Putri Mase; Rani Rani (RESEARCH FAIR UNISRI, 2024)
Abstract Talent management began to become popular in Indonesia after the President of the Republic of Indonesia, Joko Widodo, promoted it in mid-2019. The idea conveyed was that human resource development was a priority and key to Indonesia's success in the future. Talent management was formulated to be a strategy for increasing the productivity and competitiveness of human resources. There are three areas within the scope of the National Talent Management design, namely research and innovation, arts and culture, and sports. National Talent Management will seek to screen the talents and potential of young Indonesians in these three areas. National Talent Management is expected to be able to address some of Indonesia's lagging behind in human resource management. Keywords: Talent Management, Strategy, Millennial Generation